Sykepleielærere sine holdninger og kunnskapsbehov i kunnskapsbasert praksis - Utne, Inger; Leegaard, Marit; Røkholt, Gro (Nordisk tidsskrift for helseforskning, 2015)
It is required that faculty in nursing education prepares students to work evidence-based (EBP). The purposes of this study are to identify teachers’ beliefs towards EBP and to describe what the faculty identify as their specific learning needs to teach EBP. Data were collected from teachers at a University College in Norway by use of questionnaires and focus group interviews. Descriptive statistics were used to analyze the questionnaires and thematic content analysis for the focus group interviews. The teachers have positive beliefs towards EBP and their central learning needs were searching the literature, critical appraisal and application. They have knowledge in basic methodology, but need more knowledge of epidemiological and summarized research. Teaching and training in all six stages of EBP is important for teachers to develop their knowledge of EBP. Qualitative and quantitative methods in combination, works well to identify teachers’ specific needs for new knowledge.